Comparison of regulated emission factors of Euro 6 LDV in Nordic temperatures and cold start conditions: Diesel- and gasoline direct-injection. (1st June 2019) - Weber, Christian; Sundvor, Ingrid; Figenbaum, Erik
Abstract: Local air pollution in Norwegian wintertime is characterized by an increase in NO2 concentrations, due to poor dispersion and increased vehicle emissions. The focus of this study is therefore the characterisation of exhaust vehicle emissions in cold ambient temperatures. Euro 6 Gasoline Direct Injection (GDI) cars and diesel cars were tested in the laboratory in cold temperatures, including with cold start of the engine. Results show high emissions of CO2, PM and NO x . For the first time, we report also elevated NO x values for GDI vehicles. Further measurements are required to investigate whether these results are the beginning of a new trend of high NO x emissions from GDIs, or if these results represent singular events, but it may indicate that further NO x traps or catalysts are required for these vehicles. Understanding the relationship of cold ambient temperatures and vehicle emissions is also particularly important for air quality dispersion modelling, which do not currently account for emission temperature dependence. Highlights: Regulated emission factors of Euro 6 were measured in the laboratory. Test sample consists of 6 gasoline direct injection (GDI) cars and 8 diesel cars. Results confirm high NOx emission for diesel cars, up to 1417 mg/km. Some of the GDI cars show relatively high NOx values, up to 212 mg/km. Cold starts in cold temperature increase the emission of particulates for GDI.